Creep and dynamic mechanical behavior of PP-jute composites: Effect of the interfacial adhesion - Acha, Betiana Andrea (2007)
The dynamic mechanical response and the short term creep-recovery behavior of composites made from bi-directional jute fabrics and polypropylene were studied. In order to improve the compatibility of the polar fibers and the non-polar matrix, two alternatives were compared: the addition of coupling agents and the chemical modification of the fibers. In the first case, two commercial maleated polypropylenes and lignin, a natural polymer, were used. In the second approach, the fibers were esterified using a commercial alkenyl succinic anhydride. The degree of interfacial adhesion was inferred from the measured properties and confirmed by the observation of the composite fractured surface. The maleated polypropylenes acted as compatibilizers since they were able to join the fibers to the neat PP, locating themselves in the interphase region. On the other hand, a clear separation between fibers and matrix could be observed when lignin was used as compatibilizing agent and when the chemically modified fibers were used to prepare the composite. The creep deformation could be directly related to the interfacial properties. Bürgers model parameters were calculated from the creep part of the curves, and the recovery part was modeled using these values. A very good agreement between experimental data and theoretical curves were obtained in the creep region, although small discrepancies were found in the recovery part. The feasibility of the construction of a master curve (using the time-temperature principle) to predict long term creep behavior of the composites was investigated. © 2007 Elsevier Ltd. All rights reserved.